2014
DOI: 10.1016/j.envint.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl substances and lipid concentrations in plasma during pregnancy among women in the Norwegian Mother and Child Cohort Study

Abstract: Background Perfluoroalkyl substances (PFASs) are widespread and persistent environmental pollutants. Previous studies, primarily among non-pregnant individuals, suggest positive associations between PFAS levels and certain blood lipids. If there is a causal link between PFAS concentrations and elevated lipids during pregnancy, this may suggest a mechanism by which PFAS exposure leads to certain adverse pregnancy outcomes, including preeclampsia. Methods This cross-sectional analysis included 891 pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 65 publications
7
94
6
Order By: Relevance
“…During pregnancy blood lipids are substantially elevated and these changes are not believed to be atherogenic (Piechota and Staszewski, 1992). Putting clinical relevance aside our results are in line with a previous report form the Norwegian Mother and Child Cohort study (Starling et al, 2014) and the National Health and Nutrition Examination Survey 2003(Jain, 2013. Combined the results from these studies suggest that despite physiological changes associated with pregnancy (Carter 1990), both PFOS and PFOA appear to influence cholesterol level in pregnant subjects in a similar way as has been observed in non-pregnant subjects.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…During pregnancy blood lipids are substantially elevated and these changes are not believed to be atherogenic (Piechota and Staszewski, 1992). Putting clinical relevance aside our results are in line with a previous report form the Norwegian Mother and Child Cohort study (Starling et al, 2014) and the National Health and Nutrition Examination Survey 2003(Jain, 2013. Combined the results from these studies suggest that despite physiological changes associated with pregnancy (Carter 1990), both PFOS and PFOA appear to influence cholesterol level in pregnant subjects in a similar way as has been observed in non-pregnant subjects.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of magnitude the associations between both PFOS and PFOA with total serum cholesterol was comparable to that observed for high saturated fat intake during pregnancy. The positive association observed between serum concentrations of PFOS and PFOA with total cholesterol in our study is in line with what has previously been reported among the general public (Eriksen et al, 2013;Nelson et al, 2010), in highly exposed populations (Costa et al, 2009;Frisbee et al, 2010;Olsen et al, 2003;Sakr et al, 2007aSakr et al, , 2007bSteenland et al, 2009), and in pregnant women (Jain, 2013;Starling et al, 2014). The strength of the associations reported in these studies has, however, varied considerably.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…21 Clearly, the effect of PFAS exposure on the health of both mother and baby is of concern. Several studies have reported links between PFAA exposure and perturbation in lipid metabolism [22][23][24] and glucose tolerance 24 during pregnancy. Exposure to some PFAAs during early life stages has also been linked to adverse health effects such as reduced birth weight and immune toxicity.…”
Section: 20mentioning
confidence: 99%